Construction and application of the emergency resilience capability evaluation scale and model for grassroots medical workers: a cross-sectional study in Guangzhou, China - Wu, Qiaohui; Wu, Linjian; Liang, Xueqing; Xu, Jun; Liu, Li; Huang, Zhijie; Ma, Zhen (Frontiers in Public Health, 2024)
Objective Public health emergencies pose a serious challenge to the ability of medical personnel to respond. We aimed to establish a scientific and effective resilience capability assessment scale for grassroots medical workers and explore the way to improve resilience. Research design Developed a resilience ability assessment scale and applied it on the medical personnel who worked in community health service centers for more than 1 year. Related indicators were identified through literature review and the Delphi method. The established scale was given weight using the attribute analytic hierarchy process, and the evaluation model was built through the grey correlation analysis. Principal findings A three-level indicator scale was established, which included three first-level indicators [professional quality (weight 0.346), psychological capital (weight 0.614), and emergency attitude (weight 0.040)]. The second-level indicators had 13 contents and were further subdivided into 46 three-level indicators. The overall resilience ability assessment score of 347 medical workers in Guangzhou was only 0.787. However, steady scientific-exercise habits and relative training can help improve their public health emergency resilience ability (p < 0.05). Conclusion The establishment of the scale can provide a strategic basis for improving the resilience strength of grass-roots medical personnel. We should encourage this group to form a good habit of exercise, strengthen their crisis awareness by actively organizing theoretical training and practical exercises on public health emergencies, and improve their psychological capital level. Patient or public contribution In this study, 347 medical workers from 6 basic medical institutions in Guangzhou participated in the questionnaire.